TWO IMPORTANT EXTENSION THEOREMS FOR THE GAP-INTEGRAL - D. K. Ganguly; Ranu Mukherjee (IndoMS, 2011)
The concept of the GAP-integral was introduced by the authors [4]. In this paper Cauchy and Harnack extensions for the GAP integral on the real line arepresented.DOI : http://dx.doi.org/10.22342/jims.17.1.13.49-58